Organización administrativa en las cajas de ahorro de la Comunidad de Oñacapac - Ordóñez Velásquez, Wendy Lilibeth (2024)
The curricular integration work called Administrative Organization in the savings banks of the Oñacapac Community, is based on the need to make a proposal for its application within the savings banks, in this case focused on the administration of these financial institutions, proposing a model of organizational structure with their respective functions, with the purpose of contributing to the efficient development of all operations carried out by both family and community savings banks, coupling a different organizational model in both cases, adjusted to their needs, which will facilitate the administration and control of organizational management, improving its efficiency and achieving a transparent participation of all partners, in terms of organization and fundamental decision making for the financial development of these savings banks. In order to achieve the proposed objectives, a survey of the directors of the savings banks in the community of Oñacapac was used as a basis, as well as visits to the savings banks, where it was possible to identify areas for improvement in the administrative area, which facilitated the development of a model of organizational and functional structure taking into account the requirements of the members that make up the savings bank, in addition a manual of functions was also developed, detailing each position in a concise manner, the proposal also included the development of the administrative procedures necessary for a better control of the operations within the savings bank, represented in flow charts, and designing administrative policies that allow a better control of human and financial resources. Finally, methodological strategies were designed for each administrative procedure, and formats on how to apply them, to optimize the management of the members and the administration of financial resources.